Use of a Birth Plan within Woman‐held Maternity Records: A Qualitative Study with Women and Staff in Northeast Scotland. Issue 3 (21st April 2014) - Whitford, Heather M.; Entwistle, Vikki A.; van Teijlingen, Edwin; Aitchison, Patricia E.; Davidson, Tracey; Humphrey, Tracy; Tucker, Janet S.
Abstract Background Birth plans are written preferences for labor and birth which women prepare in advance. Most studies have examined them as a novel intervention or "outside" formal care provision. This study considered use of a standard birth plan section within a national, woman‐held maternity record. Methods Exploratory qualitative interviews were conducted with women (42) and maternity service staff (24) in northeast Scotland. Data were analyzed thematically. Results Staff and women were generally positive about the provision of the birth plan section within the record. Perceived benefits included the opportunity to highlight preferences, enhance communication, stimulate discussions, and address anxieties. However, not all women experienced these benefits or understood the birth plan's purpose. Some were unaware of the opportunity to complete it or could not access the support they needed from staff to discuss or be confident about their options. Some were reluctant to plan too much. Staff recognized the need to support women with birth plan completion but noted practical challenges to this. Conclusions A supportive antenatal opportunity to allow discussion of options may be needed to realize the potential benefits of routine inclusion of birth plans in maternity notes.